The evolution of chemical groups and isotopic fractionation at different maturation stages during lignite pyrolysis. (1st January 2018) - He, Kun; Zhang, Shuichang; Mi, Jingkui; Zhang, Wenlong
Highlights: Coal maturation can be identified into four stages. k∗/k for the cleavage of various chemical groups dominates isotopic fractionation. The recombination leads to the rollover of δ 13 C2 at extremely high maturity. Abstract: In this study, the evolution of different chemical groups and isotopic fractionation at different maturation stages of coals were investigated by gold-tube pyrolysis, detailed geochemical analysis and theoretical calculations based on Density Function Theory (DFT). The results from non-isothermal pyrolysis of lignite revealed that the conversion and hydrocarbon generation of lignite can be divided into four maturation stages in the range of Ro from 0.35 to 4.66%. Fourier-transform infrared spectra (FTIR) results of residual coals showed that the evolution of different functional groups dominates the generation of oil and gas products at different maturation stages. Correspondingly, the activation energy for methane generation was fitted into four Gaussian distributions, which elucidated different formation mechanisms or precursors of methane. Theoretical calculations indicated that the difference of isotopic fractionation kinetics for the cleavage of different chemical groups dominates carbon and hydrogen isotopic compositions of methane during lignite pyrolysis. By calculation of the isotopic fractionation factor (α = k∗/k) for the cleavage of ethyl and methyl radical, a simplified model was established to predict the carbon isotopic ratios of ethane (δ 13 C2 ) with and without cracking. Moreover, thermodynamic calculations confirmed that the occurrence of recombination between ethane and polycyclic aromatics is available at temperatures between 25 and 650 °C. It is also demonstrated that the isotopic exchange between ethane and methyl aromatics can occur and will result in the depletion of D for residual coals and 13 C for ethane during this process. Hence, the recombination reactions should be responsible for the rollover of δ 13 C2 at extremely high maturity both in experimental and geological conditions.